1988
DOI: 10.1111/j.1365-2672.1988.tb05097.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of psychrotrophic bacteria in raw and UHT‐treated goats'milk

Abstract: The growth of six strains of Pseudomonas fluorescens, two of Ps. fragi, and one of Serratia liquefaciens was followed in raw and UHT-treated goats' milk, held at 4 degrees C. Generation times for Ps. fluorescens in UHT milk ranged from 5.19 to 5.81 h, increasing markedly in raw milk (8.34-21.49 h). Growth of Ps. fragi did not differ significantly between raw (4.56, 4.65 h) and UHT (5.04, 7.24 h) milk. Generation times for S. liquefaciens were 6.63 and 14.07 h, for UHT and raw milk respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…[1]) was used and growth parameters were directly obtained from nonlinear regression analysis (Table 2). The maximum growth rates for storage at 4°C, 15°C, and 29°C were 0.056, 0.17, and 0.46 h −1 , respectively, and the MGT were 6.42, 2.82, and 0.81 h, respectively, which are in agreement with published data for milk (Cox and MacRae, 1988).…”
Section: Growth Curves At Constant Temperaturesupporting
confidence: 90%
“…[1]) was used and growth parameters were directly obtained from nonlinear regression analysis (Table 2). The maximum growth rates for storage at 4°C, 15°C, and 29°C were 0.056, 0.17, and 0.46 h −1 , respectively, and the MGT were 6.42, 2.82, and 0.81 h, respectively, which are in agreement with published data for milk (Cox and MacRae, 1988).…”
Section: Growth Curves At Constant Temperaturesupporting
confidence: 90%
“…is not affected by other selected groups of bacteria; however, the bacteria indigenous to food may be more vigorous and competitive. Cox & MacRae (1988) observed that the growth of some psychrotrophic strains of Pseudomonas spp. inoculated into raw milk was slower than when inoculated in UHT milk.…”
Section: Discussionmentioning
confidence: 99%
“…According to some published data, our model can also underpredict the growth rate of pseudomonads in some situations. Examples for this are the data of Cox & MacRae (1988), in inoculated UHT goats’ milk, and those of Gill & Newton (1977), in inoculated aseptically obtained meat slices. With these data, the percentage bias indicators were negative, about −25% and −11%, respectively.…”
Section: Discussionmentioning
confidence: 99%